Políticas domésticas en arenas (trans)nacionales: Abigail Mejía sobre la invasión de Estados Unidos a la República Dominicana - Yamile Silva (Les Cahiers ALHIM)
This essay analyzes five texts — a short story and four essays — that contribute to the political debates happening during the U.S invasion in the Dominican Republic, and which were published in Spanish newspapers (La Vanguardia and Hojas Selectas) as well as the Dominican paper (La Conquista) between 1918 y 1921. This essay reads these articles through an affective lens to analyze how does Abigail Mejía employ her writing to generate affects and how she manages the affects produced by the American invasion.